2004
DOI: 10.1074/jbc.m400344200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of IFI16 for the Maximal Activation of p53 Induced by Ionizing Radiation

Abstract: IFI16 is a member of the PYRIN superfamily that has been implicated in BRCA1-mediated apoptosis and inflammation signaling pathways. Here we report that most breast cancer cell lines examined expressed decreased mRNA and protein levels of IFI16, although IFI16 is expressed in human primary normal mammary epithelial cells. Significantly, immunohistochemical analysis of tissues from 25 breast cancer patients demonstrated that carcinoma cells showed negative or weaker staining of IFI16 compared with positive nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
118
2
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(131 citation statements)
references
References 34 publications
9
118
2
2
Order By: Relevance
“…Additionally, the IFI16 protein binds to p53 (27) and increased expression of the IFI16 protein in cells potentiates p53-mediated transcription of p21-luc-reporter (27). These observations (25)(26)(27) provide support for the idea that increased levels of the IFI16 protein in old cells, by potentiating p53-mediated transcription of cell cycle inhibitory genes, such as p21, contribute to senescence-associated permanent cell growth arrest. Although these observations suggest a role for IFI16 protein in p53-mediated cellular senescence, signaling pathways that contribute to transcriptional activation of the IFI16 gene during cellular senescence remain to be elucidated.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Additionally, the IFI16 protein binds to p53 (27) and increased expression of the IFI16 protein in cells potentiates p53-mediated transcription of p21-luc-reporter (27). These observations (25)(26)(27) provide support for the idea that increased levels of the IFI16 protein in old cells, by potentiating p53-mediated transcription of cell cycle inhibitory genes, such as p21, contribute to senescence-associated permanent cell growth arrest. Although these observations suggest a role for IFI16 protein in p53-mediated cellular senescence, signaling pathways that contribute to transcriptional activation of the IFI16 gene during cellular senescence remain to be elucidated.…”
Section: Introductionsupporting
confidence: 63%
“…Studies have provided evidence that increased levels of the IFI16 protein in cells potentiate p53-mediated transcription of target genes (25)(26)(27). Moreover, it has been shown that IFI16 protein is needed for p53-mediated apoptosis in certain cells following ionizing radiation -induced apoptosis (26).…”
Section: Ifi16 Is a Transcriptional Target Of P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study found that the expression of IFI16 protein is relatively low in human breast cancer cell lines and tumors (compared with normal breast epithelial cells and tissues). Furthermore, treatment of these breast cancer cell lines with 5-aza-dC resulted in up-regulation of IFI16 expression (16). Consequently, we considered the possibility that either our immunoblotting conditions to detect relatively low levels of IFI16 protein in prostate cancer cell lines were not optimum or the expression of IFI16 gene is silenced in prostate cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment of human breast cancer cell lines with 5-aza-dC has been reported to induce the expression of IFI16 gene (16), the presence of a CpG island has not been shown in the 5 ¶-regulatory region of IFI16 gene. Consistent with a role for IFI16 protein in cellular senescence-associated cell growth arrest, we have noted (5) that the expression of IFI16 protein was either very low or undetectable in most human prostate cancer cell lines tested (including LNCaP and DU-145 cell lines).…”
Section: Introductionmentioning
confidence: 99%